Hypertension prevalence, awareness, treatment and its correlates among people 35 years and older: Result from pilot phase of the Azar cohort study - Zohreh Ghorbani; Seyed Morteza Shamshirgaran; Samad Ghaffari; Parvin Sarbakhsh; Farzad Najafipou; Nayyereh Aminisani (Wolters Kluwer Medknow Publications, 2018)
Background and Objective: There is remarkable alteration in hypertension prevalence and awareness, and their correlates among various geographic locations and ethnic groups. The aim of this study was to report hypertension prevalence, awareness, and its correlates as well as hypertension treatment, and control among Azari people aged 35 years and older. Materials and Methods: The pilot phase of the Azar Cohort Study; a state level of a nationwide PERSIAN cohort study was conducted in Khameneh city between October 2014 and January 2015. All people 35 years of age and above were invited to take part in this study. A comprehensive range of different biomarkers, lifestyle, socioeconomic factors, and health-related factors was collected. Blood pressure was measured by a trained nurse/midwife. Descriptive statistical methods were used to present general characteristics of the study population as frequency tables. Separate multiple logistic regression models were built to assess the predictors of hypertension prevalence. Results: A total of 1038 people were included in this study. The overall prevalence of hypertension was 22.9%. Awareness of hypertension was 60.5% and in those with known hypertension, 84% were using the antihypertensive medications, of those 68.5% had controlled hypertension. After adjustment; age (odds ratios [OR]adj= 1.12 95% confidence interval [CI]: 1.09-1.15), gender (ORadj= 1.65 95% CI: 1.08-2.51), obesity ORadj= 2.51 (1.40-4.88), waist-to-hip ratio (WHR) (ORadj= 1.70 (1.05-2.75), and comorbidities (ORadj= 2.51 (1.72-3.66) were independent predictors of hypertension. Conclusion: Age, sex, body mass index, WHR, and comorbidities were known as predictors of hypertension in this study, health promotion strategies including lifestyle modification to reduce overweight/obesity and secondary prevention programs for early detection of hypertension in high-risk groups according to age, gender, and disease profile are recommended.